Assessment of the quality of life after surgical treatment of patients with primary postoperative ventral hernia in conditions of comorbidity - V. I. Piatnochka; S. I. Kornaha; R. S. Kohan (Kazimierz Wielki University, 2019)
Improving the quality of life of patients after surgical treatment of primary and postoperative ventral hernias is a very urgent problem, which is explained by the increasing number of patients with this pathology, high rates of recurrences and complications in hernioplasty (4.3-46 %). Objective. Improving the results of surgical treatment of patients with primary and postoperative ventral hernia under comorbidity by performing a comparative evaluation of different types of hernioplasty performed using quality of life indicators in the early and late postoperative period. Materials and methods. The quality of life indicators were analyzed based on the SF-36 questionnaire after surgical treatment of 1419 patients with primary and postoperative ventral hernia under conditions of comorbidity, operated with patient's own tissue hernioplasty, onlay, sublay, inlay, CST techniques. The total number of patients questioned on the SF-36 questionnaire on quality of life was527. In relation to all patients operated on by different methods of hernioplasty in the main group and comparison group (1419 persons), the number of patients questioned in the postoperative period was 37.14 %, ie more than a third of all patients operated for the whole period of the study (2001-2017). pp). This demonstrates the representativeness of this sample population. Results. The results of the study were found to be the most optimal for the use in the surgical treatment of primary ventral hernia (PVH) and postoperative ventral hernia (POVH) sublay and inlay technique, taking into account the lowest incidence of recurrence in their performance and the fastest recovery of the basic parameters of life of patients and quality of life in the postoperative period. The indicators of physical and psychological components of health at this time of the survey were significantly higher in patients of the main group. This is probably due to the recorded recurrence of PVH [8] after own tissue hernia. Determination of health components after 1 year showed a slight improvement in both indicators relative to the previous survey data in all study groups (p <0.05). The psychological component of health was significantly higher in patients in the main group than in patients in the comparison group. (51.73±6.37) points compared with the results of the 6-month survey, and slightly improved ((46.81±2.59) points) in the comparison group (p> 0.05). Conclusions. The results of the study seriously suggest that there is a strong correlation between the type of surgical hernioplasty techniques used in patients with  PVH and POVH the incidence of disease recurrence and, as a consequence, the quality of life of patients - an important comprehensive determinant of health.